Answer:
2x(5x + 14) + 15
Step-by-step explanation:
Given: (2[tex]x^{2}[/tex] + 3)(4x + 5) - 8x([tex]x^{2}[/tex] - 2)
(2[tex]x^{2}[/tex] + 3)(4x + 5) - 8x([tex]x^{2}[/tex] - 2) = 2[tex]x^{2}[/tex](4x + 5) + 3(4x + 5) - 8x([tex]x^{2}[/tex] - 2)
= (8[tex]x^{3}[/tex] + 10[tex]x^{2}[/tex] + 12x + 15) - 8[tex]x^{3}[/tex] + 16x
= 8[tex]x^{3}[/tex] + 10[tex]x^{2}[/tex] + 12x + 15 - 8[tex]x^{3}[/tex] + 16x
collecting like terms to have,
8[tex]x^{3}[/tex]- 8[tex]x^{3}[/tex] + 10[tex]x^{2}[/tex] + 12x + 16x + 15
10[tex]x^{2}[/tex] + 28x + 15
Thus,
(2[tex]x^{2}[/tex] + 3)(4x + 5) - 8x([tex]x^{2}[/tex] - 2) = 10[tex]x^{2}[/tex] + 28x + 15
= 2x(5x + 14) + 15